SOSIALISASI WASPADA INFEKSI CORONA VIRUS PADA LANSIA DI PANTI JOMPO RUMOH SEUJAHTRA GEUNASEH SAYANG, DINAS SOSIAL ACEH - Yanti, Budi; Priyanto, Herry; Zulfikar, T (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Coronavirus is a zoonosis disease, and person-to-person transmission built. Coronavirus infection can increased morbidity and mortality in humans. Otherwise, the aging process has many changes that characterized immunity response decrease, delayed the biological process, and decline in functional deserves. Healthy aging remains attended by some morphological and functional reduction in the respiratory system. An older person has a higher susceptibility to being infected with the coronavirus compared to young age. Currently, the world is encountering the outbreak of coronavirus infection, precisely Sars-CoV2. This activity is to increase the awareness and knowledge of the elderly in nursing homes through counseling activities. The implementing method of this activity starts with the assistance of elderly gathering in the hall and presents information related to the symptoms and preventions the coronavirus infections. This community program expects that it builds up knowledge of the elderly about the prevention of coronavirus infection, which is becoming a global epidemic today.Â